Regulatory challenges in developing long-acting antiretrovirals for treatment and prevention of HIV infection. Issue 4 (July 2015) - Arya, Vikram; Au, Stanley; Belew, Yodit; Miele, Peter; Struble, Kimberly
Abstract : Purpose of review: To outline some of the regulatory challenges inherent to the development of long-acting antiretrovirals (ARVs) for the treatment or prevention of HIV infection. Recent findings: Despite advances in drug development that have reduced ARV dosing to once daily, suboptimal drug adherence remains an obstacle to successful HIV treatment. Further, large randomized trials of once daily oral ARVs for preexposure prophylaxis (PrEP) have shown that drug adherence correlates strongly with prophylactic effect and study outcomes. Thus, the prospect of developing long-acting ARVs, which may mitigate drug adherence issues, has attracted considerable attention lately. Summary: Because of their pharmacokinetic properties, the development of long-acting ARVs can present novel regulatory challenges. Chief among them is determining the appropriate dosing regimen, the need for an oral lead-in, and whether existing data with an approved oral agent, if available, can be leveraged for a treatment or prevention indication. For PrEP, because validated biomarkers are lacking, additional nonclinical studies and evaluation of tissue concentrations in multiple compartments may be necessary to identify optimal dosages. Study design and choice of controls for registrational trials of new long-acting PrEP agents might also prove challenging following the availability of an oral PrEP drug.